Synthesis and characterization of polyether sulfone/ polyethylene glycol/ montmorillonite nano mixedmatrix membrane for removal of phosphate from water - Alansari, Ali Baderldin Abdelmilk (2017)
Eutrophication is one of the most problematic water pollution, caused by the high level of nutrients in water, mainly phosphate, which is due to the fertilizers runoff from the agricultural areas, as well as the untreated disposal of domestic and industrial wastewater into the environments. Besides, consuming high concentration of phosphate from drinking water can lead to various types of health diseases. Considering the adverse effects of phosphate pollution to human and environment, scientists and researchers had done numerous studies using different methods to remove phosphate from water, such as adsorption, extraction, flotation, precipitation, ion exchange, electro dialysis, membrane filtration and electrocoagulation. Phosphate removal using membranes based on polyether sulfone (PES), with different ratios of organically modified montmorillonite (OMMT) nanoparticles and polyethylene glycol (PEG), prepared by phase inversion method was investigated. The hydrophilicity of prepared PES membranes was studied by water content and porosity measurements. FTIR and FESEM-EDX was used to study the chemical composition as well as to ensure the phosphate absorption by the membranes. Thermal properties of the membranes were investigated by TGA and DSC. While the morphology of the membrane investigated by FESEM. Performance of prepared membranes was determined in terms of the water flux and removal by changing conditions of pressure range 1 to 3 bar and pH form 2 to 10 as well as OMMT nanoparticles concentration 1 to 7 wt.%. It was observed that increase in pressure and OMMT nanoparticles loading is inversely proportionalto the removal, and directly proportional to the water flux. Eleven different membranes, containing different ratios of PES, OMMT nanoparticles and PEG were sampled in order to prepare optimum membrane. At 1 bar pressure and 50 ppm phosphate concentration the neat PES membrane successfully achieved rejection of phosphate up to 97.6 % and water flux up to 2.26 L/m2. h whereas the optimum membrane achieved rejection of phosphate up to 94.70%, water flux up to 49.2 L/m2. h, and the optimum pH was pH4. The experimental results revealed that the PES/OMMT/PEG could have a promising performance for the phosphate removal in wastewater treatment technology.